Professional Development Through Reflective Practice: A Framework for TESOL Teachers - Farrell, Thomas S.C.; Macapinlac, Melanie (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
This paper outlines a case study of the reflections of two novice teaching English to speakers of other languages (TESOL) teachers in South Korea through the lens of a framework for reflecting on practice that included reflections on the teachers’ philosophy, principles, theory, practice, and beyond practice. Overall, the results revealed that connections between their reflections on the hidden aspects of teaching (philosophy, principles, and theory) for both teachers remained consistent with what was observed in their practices, and the connections that emerged between their reflections were grouped into two main categories: the acknowledgement of teacher roles, and the importance of their students’ success.